2014
DOI: 10.1590/0037-8682-0125-2014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections in women and their association with clinical conditions

Abstract: Introduction: Surgical site infections (SSIs) can affect body tissues, cavities, or organs manipulated in surgery and constitute 14% to 16% of all infections. This study aimed to determine the incidence of SSIs in women following their discharge from a gynecology outpatient clinic, to survey different types of SSIs among women, and to verify the association of SSIs with comorbidities and clinical conditions. Methods: Data were collected via analytical observation with a cross-sectional design, and the study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Similar to our findings, there is a significant association between obesity and diabetes mellitus and the develpomenet of SSI following CS [ 17 ]. In addition, de Araújo et al in 2014 [ 42 ] and Alfonso-Sanchez et al in 2017 [ 43 ] reported a strong positive relationship between increased risk for SSI and anemia, hypertension, obesity and diabetes mellitus. Recently, Molla et al, in 2019 [ 5 ] found that cases with pregnancy-induced hypertension (PIH) were about five times more likely to develop SSI compared to normal ones.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, there is a significant association between obesity and diabetes mellitus and the develpomenet of SSI following CS [ 17 ]. In addition, de Araújo et al in 2014 [ 42 ] and Alfonso-Sanchez et al in 2017 [ 43 ] reported a strong positive relationship between increased risk for SSI and anemia, hypertension, obesity and diabetes mellitus. Recently, Molla et al, in 2019 [ 5 ] found that cases with pregnancy-induced hypertension (PIH) were about five times more likely to develop SSI compared to normal ones.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, there is an increased risk for SSI in the presence of other comorbidities [29] explicitly: anemias, obesity [30] hypertension, diabetes mellitus as well as other associated morbidities in the patient [31].…”
Section: Discussionmentioning
confidence: 99%
“…were found in the previous study by Bhadauriya et al with E.coli as the most common responsible pathogen (36.62%) followed by Klebsiella species (6.10%). In contrast, Staphylococcus aureus was found to be the most common pathogen responsible [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%